TEACHER INCLUSIVENESS AS A FORM OF PROTECTIONBEHAVIOR SCHOOL BULLYING IN MADRASAH - Mei Wiji Amelia (Penelitian dan Pengembangan Ilmu, 2024)
School bullying behavior has shaken education in Indonesia, this was alsostated by the Minister of Education and Culture Nadiem Makarim that 24.4% ofIndonesian students experienced bullying through the 2022 National Assessment. Theimpact felt by students who experienced bullying not only reduced their academicachievement, but what is worse is mental disability. This article will answer forms ofbullying behavior, the impact of bullying behavior and teachers' efforts to overcomebullying behavior in elementary schools. The research approach used by researchers is aqualitative approach and a case study type of research. This research was conducted at MIMu'awanah Banjarwati Paciran Lamongan using data collection techniques in the form ofobservation, interviews and documentation. Meanwhile, the data analysis used in thisresearch is data reduction, data presentation, and data verification. The results of theresearch show that the forms of bullying behavior in elementary schools are direct verbalbullying, physical intimidation and indirect verbal bullying. Furthermore, the impact ofbullying behavior in elementary schools is that apart from having a negative psychologicaland physical impact on the victims, bullying behavior also has a negative impact onwitnesses and the perpetrators. The efforts that have been made as a teacher to overcomebullying behavior in elementary schools include teacher programs where the class teacheris the main counselor, class teacher strategies where the teacher acts as an advisor,motivator and makes agreements. Madrasah programs are also carried out such asproviding guidance and supervision to students, collaborating with parents (parentingprograms) such as holding meetings, and putting up the slogan